Runaway bride - Field, Tom; Rosenberg, Tom; Kroopf, Scott; Cort, Robert; McGibbon, Jossan; Parriot, Sara; Marshall, Garry 1934- (Paramount, 2000)
Roberts plays small-town girl Maggie Carpenter, wise marches down the aisle become a series of near Mrs. when she bolts before saying "I do". Gere is like Graham, a cynical, big-city newspaper columnist eager to write a tell-all story about Maggie. But the more like finds out about skittish Maggie, the more he finds he's falling in love.